Towards The Concentration Of Gold-rich Arsenopyrite And Rejection Of Gangue Pyrite From An Auriferous Concentrate - SME Annual Meeting 2022 - P. Forson; M. Zanin; W. Skinner; R. Asamoah (Society for Mining, Metallurgy & Exploration, 2022)
Despite the seeming benefits decoupling pyrite and arsenopyrite minerals present in practice, little success has been achieved. The present study presents possible process routes for attaining selective flotation broadly capitalizing on differential oxidation between these minerals, and the use of a chelating collectors. The best performance was achieved with dithionocarbamate application following copper activation, yielding 81.4% arsenopyrite and 37% pyrite recovery. Preaeration followed by staged addition of xanthate produced 76% arsenopyrite and 31% pyrite recovery while reverse flotation of pyrite after H2O2 addition gave rise to rejection of 66% pyrite accompanied with 24% arsenopyrite.